Contingency factors influencing management accounting system design of manufacturing companies in Malaysia - Siow, Yung Ern (2015)
This study examines the effect of decentralization, the adoption of advanced manufacturing technology and market competition on the adoption of sophisticated management accounting system (MAS) design and in turn, the effect of MAS design on firm performance. Subsequently, this thesis also examines the mediating effect of MAS design on the relationship between decentralization, the adoption of advanced manufacturing technology and market competition with firm performance. It follows the contingency theory to propose that decentralization causes firms to adopt sophisticated MAS design in order to ensure that controls at all levels are exerted and to ensure that relevant information are provided while the adoption of advanced manufacturing technology encourages the adoption of sophisticated MAS design in order to obtain more accurate cost data and market competition encourages the adoption sophisticated MAS design in order to assist firms to cope with both local and international competition. Thus, this research proposes a positive relationship between the three independent variables known as decentralization, the adoption of advanced manufacturing technology and market competition on MAS design and subsequently a positive relationship between MAS design and firm performance. MAS design is also proposed to be a mediator in the relationship between the three independent variables and firm performance. Using survey data from 137 manufacturing companies and regression analysis, the result shows a significant and positive relationship between the adoption of advanced manufacturing technology and market competition with MAS design and in the relationship between MAS design and firm performance. This suggests that the adoption of sophisticated MAS design is able to assist firms to cope with the changes in the manufacturing technology and assist firms to cope with the intensity of the market competition in Malaysia. However, a positive but insignificant relationship was observed in the relationship between decentralization and MAS design and MAS design was not found to be a mediator in any of the relationships above. These results have contributed to the management accounting change literature by providing empirical evidence that the adoption of advanced manufacturing technology and market competition affects the MAS design of a firm and subsequently affects the firm's performance in the context of manufacturing firms in Malaysia.